2013
DOI: 10.1371/journal.pone.0078532
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Antigen-Specific Immune Response in Patients with Multiple Sclerosis Responding to IFNβ-Therapy

Abstract: BackgroundInterferon-beta (IFNβ) regulates the expression of a complex set of pro- as well as anti-inflammatory genes. In cohorts of MS patients unstratified for therapeutic response to IFNβ, normal vaccine-specific immune responses have been observed. Data capturing antigen-specific immune responses in cohorts of subjects defined by response to IFNβ-therapy are not available.ObjectiveTo assess antigen-specific immune responses in a cohort of MS patients responding clinically and radiologically to IFNβ.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…Rates of protection after influenza immunization in patients receiving interferon beta have been reported to be unchanged in several studies , as confirmed in the present study. This applies for all post‐vaccination time points.…”
Section: Discussionsupporting
confidence: 89%
“…Rates of protection after influenza immunization in patients receiving interferon beta have been reported to be unchanged in several studies , as confirmed in the present study. This applies for all post‐vaccination time points.…”
Section: Discussionsupporting
confidence: 89%
“…A single‐strain analysis demonstrated seroprotection rates against H3N2 in patients receiving IFN comparable to those achieved in of healthy controls (93.0% vs 90.9%, n = 86) . In a study of patients with reduced clinical and radiological MS disease‐activity under IFN therapy, the immune response to influenza vaccination was similar to the one seen in healthy controls …”
Section: Resultsmentioning
confidence: 70%
“…Inactivated influenza vaccines are thus considered safe and are recommended in national guidelines . The response to influenza vaccination in MS patients has been evaluated for some of the DMT in controlled settings . Only recently the important question of response to vaccination in comparison across different therapies in a real‐life setting was raised and first results were published …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Positive responses to influenza vaccine also have been observed with other treatments for RRMS. 6,[16][17][18][19] A similar proportion of patients with MS who were or were not treated with interferon beta-1a mounted an appropriate immune response to inactivate the influenza vaccine, and no new safety concerns were noted. 18 In an exploratory study of immunomodulatory treatments, rates of protection were lower in patients treated with glatiramer acetate, natalizumab, …”
Section: Discussionmentioning
confidence: 99%